The Characteristics of Patient with Macular Hole After Pars Plana Vitrectomy (PPV) and Internal Limiting Membran (ILM) Peeling in Cicendo Eye Hospital National Eye Center, Bandung - Rani Pitta Omas (Indonesian Vitreoretinal Society, 2019)
Introduction : Macular hole (MH) can cause severe visual disturbance, but remarkable progress has been achieved in surgical treatment for eyes with this condition. Vitrectomy with internal limiting membrane (ILM) peeling allows a very high success rate for MH closure (approaching 90%). To compare characteristics patients with closed and unclosed macular hole after pars plana vitrectomy (PPV) surgery and internal limiting membran (ILM) peeling. Method : This was retrospective study which data was obtain from patient’s medical records who underwent PPV and ILM peeling since July 1st to December 31th 2018. Results : 27 eyes from 25 patients had MH surgery. 20 eyes (74%) had closed MH and 7 (26%) eyes unclosed MH after surgery. HFF value before surgery was 1,34 ± 0,90 and MHI was 1,09 ± 0,81 in closed MH. Meanwhile in unclosed MH, HFF value before surgery 0,53 ± 0,12 and MHI was 0,75 ±0,10. MHI ≥0,5 and HFF value ≥ 0,9 had a good prognostic factor. Conclusion : Despite of good prognostic factor from OCT measurement and achieve anatomical success, foveal microstructure also important in visual recovery after MH surgery.